Overview of female healthcare providers’ outlooks on cervical cancer screening: a narrative review - Wubishet Gezimu; Ababo Demeke; Firomsa Bekele; Solomon Seyife Alemu; Lema Fikadu; Addisalem Workie Demsash; Geleta Nenko Dube; Gemeda Wakgari Kitil; Elias Ezo (Frontiers in Oncology)
BackgroundCervical cancer is the second most frequent gynecologic cancer. Uniquely, it is easily preventable and treatable cancer if identified early. The insights of healthcare providers about cervical cancer screening have a crucial role in prevention and treatment. However, there has been limited literature on the providers’ perspectives on cervical cancer screening.ObjectiveThis review narrated the female healthcare providers’ (FHCPs’) outlooks on cervical cancer screening in terms of risk perceptions, awareness, knowledge, attitude, practice, and possible barriers.MethodsA thorough literature search was conducted to identify studies conducted on female healthcare providers’ overview of the perceived risk of cervical cancer, cervical cancer screening awareness, knowledge, attitude, and practice, as well as barriers to cervical cancer screening. Databases such as PubMed, Medline, Embase, Virtual Health Library, and Google Scholar were used to search for articles.ResultsAccordingly, this review identified that female healthcare providers have a low perceived risk of the disease, poor awareness and knowledge, unfavorable attitudes, and low uptake of screening practices. Furthermore, this review highlights the obstacles to cervical cancer screening acceptance, such as service inaccessibility, a lack of training and education, and fear of the procedure and results.ConclusionThis narrative review described the variable distribution of the FHCPs’ perceived risk of acquiring cervical cancer (CC). Poor knowledge and screening practices were observed. Moreover, the barriers to cervical cancer screening uptake were described. Given that healthcare providers are on the frontlines (act as role models) in increasing the community’s cervical cancer screening uptake, we suggest concerned bodies increase screening access and implement staff training programs. In addition, further mixed studies should be considered to deeply understand the possible attributes ingrained in individual and social belief systems.